WIKI: promoting collaborative writing among students in a vocational college / Tumadhir Zaid - Zaid, Tumadhir (2013)
This study is aimed at investigating the students' experience of using wiki in a collaborative writing project. The participants (n=146) were first semester students enrolled in a vocational college. During their wiki experience, ninety respondents used a wiki platform (www.wikispaces.com) to complete a writing task. Students were allowed to develop their own wiki pages based on the writing instructions. After the wikiexperience the students responded to a set of questionnaire and some students were selected for focus group interview. Findings suggest that the students viewed that wiki brings benefits to them, even though there were some issues arises. The results also revealed that the students considered the wiki features are user-friendly. The result showed that students deemed that wiki motivated them to write and changed their attitudes towards writing. It was also revealed that students found wiki had functioned as collaborative writing tool and facilitated them for the collaborative writing. Overall findings for the present study suggest that wiki promoted collaborative writing therefore some implications should be given attention by the school administrators, educators,parents, as well as the wiki providers. It is recommended that school administrators should provide enough facilities and educators should design meaningful lessons and deliver clear instructions to facilitate the students. The parents are advice to give encouragement and the wiki providers need to upgrade physical look of the wiki pages.Suggestions, for future research include investigating the effect of wiki on other ESL skills and on the curriculum. Future research may also gauge the teachers' acceptance and readiness to utilise wiki in their classrooms.